Economic evaluation of toripalimab combined with chemotherapy in the treatment of non-small cell lung cancer - Wang, Hao; Long, Yunchun; Xu, Yuan; Liao, Li; Zhou, Yujie (Frontiers in Public Health, 2023)
Background and Objective: The CHOICE-01 trial showed that toripalimab plus chemotherapy achieved satisfactory outcomes compared with chemotherapy in patients with advanced non-small cell lung cancer (NSCLC) who were negative for driver genes, but the economics of this regimen is unclear. Therefore, this study aimed to evaluate the cost-effectiveness of toripalimab in combination with chemotherapy in advanced NSCLC with negative driver genes from the perspective of the Chinese healthcare system. Materials and Methods: A three-state partitioned survival model was developed to simulate the costs and outcomes associated with adding toripalimab to first-line chemotherapy. The clinical data in the model came from the CHOICE-01 trial, only direct medical costs were included, and utility values were referred to the literature. Four models were applied to explore the differences in the results of fitting and extrapolating K-M curves from different models, and cost-effectiveness subgroup analysis was performed. The incremental cost-effectiveness ratio (ICER) was used as the main outcome measure. Sensitivity analysis was performed to assess the impact of parameter uncertainty on the model. Results: The baseline analysis showed that toripalimab coupled with chemotherapy cost 21,052 more than chemotherapy (43,197 vs 22,145) and also gained 0.71 QALYs more (1.75 QALYs vs 1.03 QALYs), with an ICER of 29,478/QALYs. At the current willingness-to-pay threshold (35,108/QALY), the extra cost was well worth it. The results of fitting and extrapolating the survival curves using other models were consistent with the results of the standard parametric model. Subgroup analysis demonstrated that the addition of toripalimab to chemotherapy was economical. Sensitivity analysis showed that the utility values of PD and PFS stages had the greatest impact on the model. Conclusion: From the viewpoint of the Chinese healthcare system, toripalimab combined with chemotherapy in the treatment of advanced NSCLC with negative driver genes was likely to be cost-effective compared with chemotherapy.